2021
DOI: 10.1016/j.jhin.2020.10.020
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of influenza virus in air samples of patient rooms

Abstract: Background Understanding the transmission and dispersal of influenza and respiratory syncytial virus (RSV) via aerosols is essential for the development of preventative measures in hospital environments and healthcare facilities. Methods During the 2017-2018 influenza season, patients with confirmed influenza or RSV infections were enrolled. Room air samples were collected close to (0.30 m) and far (2.20 m) from the patient’s head. Real-time polymerase chain reaction (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…In the 1980s it was demonstrated that healthy individuals only became infected upon self-inoculation after touching contaminated surfaces, or through close contact with infected infants, but not by solely sitting in the same room at a distance of > 1.8 m away from the patient’s bed [ 11 ]. These observations were later supported by several air sampling studies, in which RSV was detected infrequently, or not at all, in the air around infected patients [ 12 15 ]. In contrast to these studies, Aintablian and colleagues were able to collect RSV RNA from the air around RSV infected patients between 0.3 and 7 m away from the patient’s head, with a higher likelihood of RSV detection close to the patient [ 16 ].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In the 1980s it was demonstrated that healthy individuals only became infected upon self-inoculation after touching contaminated surfaces, or through close contact with infected infants, but not by solely sitting in the same room at a distance of > 1.8 m away from the patient’s bed [ 11 ]. These observations were later supported by several air sampling studies, in which RSV was detected infrequently, or not at all, in the air around infected patients [ 12 15 ]. In contrast to these studies, Aintablian and colleagues were able to collect RSV RNA from the air around RSV infected patients between 0.3 and 7 m away from the patient’s head, with a higher likelihood of RSV detection close to the patient [ 16 ].…”
Section: Introductionmentioning
confidence: 59%
“…Moreover, in a recent study by Chamseddine et al, none of the collected air samples around RSV infected patients were positive for RSV RNA, while half of the air samples collected around influenza A virus-infected patients were positive for influenza virus RNA. However, attempts to isolate infectious influenza virus from these samples were not successful [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent study by Chamseddine et al, none of the collected air samples around RSV infected patients were positive for RSV RNA, while half of the air samples collected around in uenza A virus infected patients were positive for in uenza virus RNA. However, attempts to isolate infectious in uenza virus from these samples were not successful(15).Contrasting results were previously reported byKulkarni et al, where air sampling around infants with RSV-con rmed bronchiolitis in general wards of a pediatric hospital resulted in the collection of high amounts of infectious RSV from the air…”
mentioning
confidence: 58%
“…Moreover, in a recent study by Chamseddine et al, none of the collected air samples around RSV infected patients were positive for RSV RNA, while half of the air samples collected around in uenza A virus infected patients were positive for in uenza virus RNA. However, attempts to isolate infectious in uenza virus from these samples were not successful (15).…”
Section: Rsv In Air and On Surfacesmentioning
confidence: 99%
See 1 more Smart Citation